Effects of Recombinant SARS-CoV-2 Spike Protein Variants on Platelet Morphology and Activation - Vettori, Marco; Carpenè, Giovanni; Salvagno, Gian Luca; Gelati, Matteo; Dima, Francesco; Celegon, Giovanni; Favaloro, Emmanuel J.; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2023)
Platelets are central elements of hemostasis and also play a pivotal role in the pathogenesis of thrombosis in coronavirus disease 2019. This study was planned to investigate the effects of different severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) recombinant spike protein variants on platelet morphology and activation. Citrated whole blood collected from ostensibly healthy subjects was challenged with saline (control sample) and with 2 and 20 ng/mL final concentration of SARS-CoV-2 recombinant spike protein of Ancestral, Alpha, Delta, and Omicron variants. Platelet count was found to be decreased with all SARS-CoV-2 recombinant spike protein variants and concentrations tested, achieving the lowest values with 20 ng/mL Delta recombinant spike protein. The mean platelet volume increased in all samples irrespective of SARS-CoV-2 recombinant spike protein variants and concentrations tested, but especially using Delta and Alpha recombinant spike proteins. The values of both platelet function analyzer-200 collagen-adenosine diphosphate and collagen-epinephrine increased in all samples irrespective of SARS-CoV-2 recombinant spike protein variants and concentrations tested, and thus reflecting platelet exhaustion, and displaying again higher increases with Delta and Alpha recombinant spike proteins. Most samples where SARS-CoV-2 recombinant spike proteins were added were flagged as containing platelet clumps. Morphological analysis revealed the presence of a considerable number of activated platelets, platelet clumps, platelet-monocyte, and platelet-neutrophils aggregates, especially in samples spiked with Alpha and Delta recombinant spike proteins at 20 ng/mL. These results provide support to the evidence that SARS-CoV-2 is capable of activating platelets through its spike protein, though such effect varies depending on different spike protein variants.
Keywords: SARS-CoV-2; COVID-19; thrombosis; platelets; aggregation; activation